Discourse for Transition toward Sustainability Development in Industrial Ecology Context in Kutai Kartanegara - Dhyna Apriyanti Walidi (The Journal of Indonesia Sustainable Development Planning, 2021)
A rich ecological value area within East Kalimantan, Kutai Kartanegara, represents a specific-particular ecological system of an island in a tropical country. Covered by the evergreen forest in the past, it has a closed-loop system formed naturally due to its metabolism. This system maintains the high diversity of nature which provides abundant resources both renewable and non-renewable. Owing to its ecological system value, the earth has been numerous beneficial the economic sector both for country and region for decades. Let say coal is one of the attractive resources for the energy sector, which has been contributing over 80% of the GDRP of Kutai Kartanegara in 2010.